Optical coherence tomography of the retina combined with color Doppler ultrasound of the tibial nerve in the diagnosis of diabetic peripheral neuropathy - Chen, Weimiao; Wu, Xiaohong; Li, Shilin; Zhang, Yan; Huang, Yinqiong; Zhuang, Yong; Bai, Xuefeng; Chen, Xiaoyu; Lin, Xiahong (Frontiers in Endocrinology, 2022)
Objective: To investigate the value of the retinal nerve fiber layer (RNFL) thickness in optic disc and the cross-sectional area (CSA) of lower limb nerves in the diagnosis of diabetic peripheral neuropathy (DPN) separately and in combination. Methods: A total of 140 patients with type 2 diabetes were enrolled, including 51 patients with DPN (DPN group) and 89 patients without DPN (NDPN group). Clinical data and biochemical parameters were collected. Electromyography/evoked potential instrument was performed for Nerve Conduction Study (NCS). Optical coherence tomography (OCT) was performed to measure the RNFL thickness of the optic disc. Color Doppler Ultrasound (CDUS) was performed to measure CSA of lower limb nerves. Results: The RNFL thickness was lower and the CSA of tibial nerve (TN) in the DPN group was larger than that in the NDPN group. The Album/Urine Creatinine Ratio (ACR), diabetic retinopathy (DR) and CSA of TN at 3cm were positively correlated with DPN. The RNFL thickness in the superior quadrant of the optic disc was negatively correlated with DPN. For RNFL thickness to diagnose DPN, the area under the curve (AUC) of the superior quadrant was the largest, which was 0.723 (95% confidence interval (CI) 0.645-0.805), and the best cut-off value was 127.5μm (70.5% sensitivity; 72.1% specificity). For CSA of TN to diagnose DPN, the AUC of the distance of 5cm was the largest, which was 0.660 (95% CI 0.575-0.739), and the best cut-off value was 13.50mm2(82.0% sensitivity; 41.6% specificity). For the combined index, the AUC was greater than that of the above two indicators, which was 0.755 (95% CI 0.664-0.846), and the best cut-off value was 0.376(64.3% sensitivity; 83.0% specificity). Conclusions: Patients with DPN have a reduction of the RNFL thickness and an increase in the CSA of the TN, and these two changes are related to DPN. The RNFL thickness of the optic disc and CSA of the TN can be used as diagnostic indicators of DPN, and the combination of the two indicators has a higher diagnostic value.